Principles of Corporate Finance - Brealey, Richard A.; Myers, Stewart C.; Marcus, Alan J (New York, 2007)
This book is about corporate finance. It focuses on how companies invest in real assets and how they raise the money to pay for these investments. Financial management is important, interesting, and challenging. It is important because today's capital investment decisions may determine the businesses that the firm is in 10, 20, or more years ahead. Also, a firm's success or failure depends in large part on its ability to find the capital that it needs.
Keywords: Corporations- Finance